MODEL APLIKASI PENGUKURAN KINERJA PERGURUAN TINGGI SWASTA DENGAN MENGGUNAKAN PERFORMANCE PRISM (STUDI KASUS PADA 2 PERGURUAN TINGGI) - Melinda Haryanto; Rousilita Suhendah; Stevanus Adree Cipto Setiawan (Universitas Kristen Krida Wacana, 2018)
In the face of increasingly fierce competition, Higher Education is required to improve itself in order to improve the quality and competence of the output therefore it can compete in the labor market. To realize this purpose, each University should need to assess their own performance so that they can see what needs to be improved and enhanced. This research aims to design a performance measurement University using Performance prism model. Private Universities are taken as sample are University with A accreditation and B accreditation. Data Analysis Methods using the identification of Key Performance Indicator (KPI), Hierarchy Analytical Process (AHP) and assessment of performance with Scoring System (Omax). Results of university’s design performance measurement using Performance prism are 39 elements of performance indicators or KPIs that consists strategies, processes and capabilities criteria which each of the 13 units consisting of: 3 KPI stakeholder students, 3 KPI stakeholder lecturers, 3 KPI stakeholder foundations, 2 KPI stakeholder supplier (book publishers) and 2 KPI stakeholder alumni. From the calculation of performance measurement using Objective Matrix obtained value of the company’s performance for university with A accreditation is 7.57 and university with B accreditation is 7.45. Keywords: Performance Prism Model ; Key Performance Indicator (KPI), Analytical Hierarchy Process (AHP) and Scoring System (OMAX)